Female Racial and Linguistic Exploitation Through Economics: A Marxist Feminist Analysis of Kamila Shamsie’s Selected Works - Mirza Noman Shamas (University of Chitral Journal of Linguistics and Literature, 2020)
Regardless of quality education, alteration of conservative era into modernization and escalatingthe streamers of gender equality, women are still standing at the verge of being victim of cruelty,injustice, malice, forced marriages, sexual violence and hatred. The law enforcement agenciesthemselves become part of exploiting women’s rights, co-modifying them and reinforcing thestereotype in this patriarchal society. When discussing the fate of women it matters less whetherthey are the women of East or West. Culture change, place change, traditions and values change,but the thing that never change is the behavior of community towards women. However, womenare going to become abandoned or protagonist, it depends upon the inner courage of women. Foran instance, women become helpless and start feeling them as the caged birds that can never flewindependently. On the other hand, some women refuse to become the part of darkness and decideto become spark in nightfall. Moreover, Pakistan is land of tremendous examples about suchwomen. Since the dawn history of human beings, subjugation towards the identity of women’sstatus has been observed in different communities and cultures. Additionally, this subjugation isdeeply rooted and exists on a large scale in Pakistani society. Therefore, this proposed study isthe splendid reflection of this acrimonious datum by ascertaining our point of view with thebounteous examples from the stories of “Burnt Shadows”, “Broken Verses” and “Home Fire” byKamila Shamsie. This study will be a milestone for presenting the women’s condition inPakistan and clearing the depiction that in developing countries like Pakistan, women are onlyvictims of cruelty. For this purpose, Marxist’s interpellation theory was used to enlighten thefeminist, race and language analysis by using the primary and secondary sources for datacollection. Results concluded on the basis detailed analysis of all the novels explain that thesystematic flow in the lives of women that is hidden in the generosity of world that can rampantthe prestige of humanity up to great extent.